The Usefulness of Subcutaneous Infiltration of Epinephrine-Containing Lidocaine for Curative Transarterial Embolization of Dural Arteriovenous Fistula: A Technical Note - Yamauchi, Shigeru (Centauro S.r.l., 2014)
Recently, transarterial embolization (TAE) with liquid embolic materials has been recognized as one of the curative therapeutic options for non-sinus type dural arteriovenous fistula (d-AVF). To prevent glue fragmentation and incomplete obliteration, flow reduction of transosseous high-flow feeders is one of the key points of this therapy. However, flow reduction of transosseous feeders is sometimes difficult with previously reported techniques such as particle embolization, manual compression, or proximal balloon occlusion. This report introduces a new technique to reduce the flow of transosseous feeders using epinephrine-containing lidocaine, and describes a case of intracranial d-AVF successfully treated with this technique. The usefulness and efficacy of the technique are discussed.